1967
DOI: 10.1029/jz072i012p03089
|View full text |Cite
|
Sign up to set email alerts
|

Proton-irradiation darkening of rock powders: Contamination and temperature effects, and applications to solar-wind darkening of the Moon

Abstract: Darkening of silicate rock powders by bombardment with 2‐ to 16‐kev protons was found to be slight unless proton flux or total proton incident‐power density is sufficient to produce sample surface temperature in excess of about 150°C. Darkening then increases with incident power density for a given proton dose; i.e., the darkening is rate dependent as well as dose dependent. The darkening is due to contamination by (1) carbon from irradiation decomposition of hydrocarbon vacuum contaminants and/or (2) metal at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1967
1967
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Surface darkening. Whether visible surface darkening, caused by ion bombardment on lunar fines, mineral powders, and glass beads, is a real or anomalous phenomena has long been debated [Rosenberg and Wehner, 1964;Hapke, 1966Hapke, , 1968Hapke, , 1973KenKnight et al, 1967;Nash, 1967;Lord, 1968;Dybwad, 1971;Yin et al, 1972;Hapke et al, 1975;Hapke and Cassidy, 1978;Pillinger and Jull, 1978;Benedix, 1993]. Experimenters who derive a null result have suggested that the darkening is not necessarily due to the irradiation but to poor vacuum, hydrocarbon contamination, or vitrification.…”
Section: Reflectance Measurements the Chemical Changes In Olivine Imentioning
confidence: 99%
“…Surface darkening. Whether visible surface darkening, caused by ion bombardment on lunar fines, mineral powders, and glass beads, is a real or anomalous phenomena has long been debated [Rosenberg and Wehner, 1964;Hapke, 1966Hapke, , 1968Hapke, , 1973KenKnight et al, 1967;Nash, 1967;Lord, 1968;Dybwad, 1971;Yin et al, 1972;Hapke et al, 1975;Hapke and Cassidy, 1978;Pillinger and Jull, 1978;Benedix, 1993]. Experimenters who derive a null result have suggested that the darkening is not necessarily due to the irradiation but to poor vacuum, hydrocarbon contamination, or vitrification.…”
Section: Reflectance Measurements the Chemical Changes In Olivine Imentioning
confidence: 99%
“…Several low-energy ion irradiation experiments on minerals have been performed to simulate the solar wind impact on surfaces (Nash, 1967;Hapke, 1973;Dukes et al, 1999). Hapke first pointed out that different effects should occur for powder-like regoliths than for compact rock surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory studies have been generally successful in reproducing the space weathering characteristics seen in lunar and S‐type asteroid spectra by focusing on the changes caused by energetic ions and micrometeorite hypervelocity impacts. Using keV protons as a solar wind analog, early studies (Nash ; Hapke ) showed that irradiation caused the reflectance spectrum of the analog and returned lunar samples to evolve toward the in situ lunar soil spectra, becoming darker, redder, and having attenuated absorptions. Through more detailed studies (see Hapke for a review), Hapke was able to show that to create spectral changes consistent with space weathering, the sample needed to contain Fe.…”
Section: Introductionmentioning
confidence: 99%